The Connectedness of the Coronavirus Disease Pandemic in the World: A Study Based on Complex Network Analysis - Zhu, Sha; Kou, Meng; Lai, Fujun; Feng, Qingxiang; Du, Guorong (Frontiers in Physics, 2021)
Since the coronavirus disease (COVID-19) pandemic started at the beginning of 2020, it has seriously affected various countries’ economic and social development and accelerated the economic recession worldwide. Therefore, the connectedness of the global COVID-19 network across countries is studied in this article. Based on COVID-19 correlations in 122 countries, we construct a complex network of COVID-19 from January 19, 2020, to August 15, 2020. We then deconstruct the overall global network connectedness and analyze the connectedness characteristics. Moreover, we empirically investigate the network connectedness influencing factors by using various countries’ macroeconomic and social data. We find that the global COVID-19 pandemic network has some prominent complex network properties, such as low path length, high clustering, and good community structure. Furthermore, population density, economic size, trade, government spending, and quality of medical treatment are significant macrofactors affecting COVID-19 connectedness in different countries.